The importance of virtual platforms in online education - Quevedo de Pérez, Ana Guadalupe
This report allows us to analyze the virtual platforms that have come to change and improve the learning process in students, being very important tools in online education that changed the face of traditional classrooms, making learning more effective and education more accessible than ever. Therefore, virtual platforms have provided many benefits through their use. In addition, traditional education has been modified by a more innovative approach and this implementation expands by being an opportunity to update the support and development of education to facilitate learning in virtual environments in the classroom. Online education has gained prominence in recent years due to the pandemic covid 19 that altered the educational system that performed normally in schools, institutes, colleges, and universities radically and forcibly changing the old methodologies applying the sudden and unexpected change, following a path of new panoramas of improvement despite the distance and the need to continue with the learning of students, promoting academic growth through virtual platforms thus giving way to technology in its maximum expression as a new projection into the future. Therefore, online education forms a key piece for teachers and students to interact in their necessary roles by adding virtual platforms for communication and elaboration of specific activities to be followed.